Implementation of kansei engineering in the design of packaging design elements: study case for Food MSME - Sari, Novi Purnama; Rahmadianto, Muhammad Athariq; Ramadhan, Raihan Thoriq; Napitupulu, Yesaya Firdaus (Universitas Mercu Buana, 2025)
The current packaging of Rangi Cake products in the market is criticized for its simplicity and lack of adequate safety features, which compromises both product safety and visual appeal. To address this, a research initiative was undertaken to enhance the design and functionality of Rangi Cake packaging. The study employed Kansei engineering to discern consumer preferences regarding packaging. The findings incorporated 46 packaging samples and identified 44 Kansei words. Utilizing Principal Component Analysis (PCA), two design concepts emerged: